Levodopa-responsive chorea: A review - Mark Farrenburg (Annals of Indian Academy of Neurology, 2020)
Background: Chorea is one of the disabling movement disorders, and the number of drugs which can treat this disorder effectively is limited. Tetrabenazine and deutetrabenazine are the two drugs approved by the US-FDA for the treatment of chorea associated with HD. Levodopa can improve chorea in some disorders, and this review aims to provide information on the use of levodopa in chorea. Methods: A literature search was performed in February 2019 using the following terms “levodopa chorea,” “levodopa TITF-1,” levodopa brain-lung-thyroid syndrome,” and “levodopa Huntington's Disease.” The information regarding the etiology, outcome, and dose of levodopa was collected. Results: We found a total of 18 cases in the literature where the benefit was reported with levodopa. Majority of the cases were brain-thyroid-lung (BTL) syndrome (50%). Another 5 cases were HD (Huntington's Disease), one with PCH type 2 (Pontocerebellar hypoplasia type 2), one with meningovascular syphilis, and two patients with Sydenham chorea. The patients with BTL syndrome responded to a very low dose of levodopa. Discussion: This review suggests that levodopa has the potential to improve chorea in BTL syndrome while its use in chorea due to other disorders requires further study. BTL syndrome due to NKX2-1 mutation responded to levodopa while we did not find any case of chorea due to ADCY-5 mutation responding to levodopa.